2004
DOI: 10.1074/jbc.m309698200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Smad2-, Smad3-, and ERK-dependent Pathways in Transforming Growth Factor-β1 Regulation of Pancreatic Stellate Cellular Functions

Abstract: Pancreatic stellate cells (PSCs) play a major role in promoting pancreatic fibrosis. Transforming growth factor-␤ 1 (TGF-␤ 1 ) regulates PSC activation and proliferation in an autocrine manner. The intracellular signaling pathways of the regulation were examined in this study. Immunoprecipitation and immunocytochemistry revealed that Smad2, Smad3, and Smad4 were functionally expressed in PSCs. Adenovirus-mediated expression of Smad2, Smad3, or dominant-negative Smad2/3 did not alter TGF-␤ 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 27 publications
5
91
0
1
Order By: Relevance
“…15,47,48 The same is true for HSC, where contrasting data describing the influence of TGFb1 on proliferation, ranging from growth inhibition to stimulation of proliferation, have been published, although the majority of publications report a TGFb1-induced growth inhibition in HSC. 44,[49][50][51] These differences may be attributed to different RT-PCR demonstrated that cultivation of immortalized PSC on Matrigel (M) for 7 days resulted in a marked decrease of Col I, TGFb1 and CTGF expression compared to cultivation on tissue culture (TC) plates, whereas aSMA expression was not altered significantly by this cultivation conditions, the housekeeping gene RPL13A served as control (a).…”
Section: Deactivation Of Pancreatic Stellate Cells R Jesnowski Et Almentioning
confidence: 90%
“…15,47,48 The same is true for HSC, where contrasting data describing the influence of TGFb1 on proliferation, ranging from growth inhibition to stimulation of proliferation, have been published, although the majority of publications report a TGFb1-induced growth inhibition in HSC. 44,[49][50][51] These differences may be attributed to different RT-PCR demonstrated that cultivation of immortalized PSC on Matrigel (M) for 7 days resulted in a marked decrease of Col I, TGFb1 and CTGF expression compared to cultivation on tissue culture (TC) plates, whereas aSMA expression was not altered significantly by this cultivation conditions, the housekeeping gene RPL13A served as control (a).…”
Section: Deactivation Of Pancreatic Stellate Cells R Jesnowski Et Almentioning
confidence: 90%
“…Through gene sequence detection, we found that the TGF-β l , Smad2/3, CycA, and ORC genes of PSC sequences were differentially expressed after co-culture with IkBαM-MSCs. Ohnishi et al (2004) found that TGF-b l promotes the activation of PSCs through the Smad2-dependent pathway and that PSCs infected by the adenovirus with the Smad2-dominant-negative gene inhibit PSC activation. IkBαM-MSCs can reduce the secretion of TGF-b 1 , thereby inhibiting the transduction of the TGF-b l -smad-2/3 signaling pathway.…”
Section: Mensenchymal Stell Cells In Chronic Pancreatitismentioning
confidence: 99%
“…Multiple studies have identified several major signaling pathways involved in the regulation of PaSC function (27,43,47,(50)(51)(52). MAPKs are key mediators of activating signals initiated by growth factors, angiotensin II, and ethanol (51,52).…”
Section: Mediators Of Pasc Activationmentioning
confidence: 99%